African economic integration: Assessing the tripartite free trade area - Dorra, Hoda Ahmed (AUC Knowledge Fountain, 2018)
In 2015, Member States of COMESA, EAC and SADC signed the Tripartite FTA to integrate their three RECs into a single market "from Cape to Cairo". The agreement came in response to many challenges that faced the three communities in their integration programs, specifically challenges related to market integration and overlapping membership. Using qualitative data, this paper studies the economic integration model of COMESA, and the Tripartite FTA The paper argues that many of the challenges that faced COMESA within its integration plan have been accounted for within the Tripartite FTA, especially the problems related to overlapping membership and economic development of Member States. However, for the tripartite integration plan to be successful, it is necessary that it replaces the original three RECs on the long run, in addition to becoming the foundation upon which the Continental FTA is built in order to create a broader form of economic integration in the continent.